Agricultural technologies for market-led development opportunities in the 1990s - Barghouti, Shawaki M.; Cromwell, E.; Pritchard, Anthony J. (Washington, D.C. : World Bank, 1993)
The main lesson in this volume is that traditional models for technology generation and dissemination require serious assessment
Includes bibliographical references.
osc 25/08/2021
Loans
Keywords: Agricultural innovations; Agricultural industries